Decision Analysis for Managers - Charlesworth, David (Business Expert Press, 2013)
Ebook from IG Library ; Everybody has to make decisions--they are unavoidable. Yet we receive little or no education or training on how to make decisions. Business decisions can be dif_ cult: which people to hire, which product lines or facilities to expand and which to sell or shut down, which bid or proposal to accept, which process to implement, how much R&D to invest in, which environmental projects should receive the highest priority, etc. This book gives you all the tools you need to... * clarify and reach alignment on goals and objectives and understand trade-offs in reaching those goals, * develop and examine alternatives, * systematically analyze the effects of risk and uncertainty, and * maximize the chances of achieving your goals and objectives. Success (getting what you want) depends on luck and good decision making. You can't control your luck, but you can maximize your odds by making the best possible decisions, and this book gets you there. Broadly speaking, this book organizes and presents otherwise formal decision-making tools in an intuitively understandable fashion. The presentation is informal, but the concepts and tools are research-based and formally accepted.